Effectiveness of Students' Learning of Research Methodology in Compiling Dissertations - purnomo, Vicki Dwi; Irwansyah, Irwansyah; Krismiyarsi, Krismiyarsi (MultiTech Publisher, 2024)
This study aims to evaluate the effectiveness of learning research methodology for postgraduate students in compiling a dissertation. The methodology used is a descriptive approach with a combination of quantitative and qualitative. Data were collected through questionnaires distributed to 100 students and in-depth interviews with 10 supervisors. The results of the study indicate that a good understanding of research methodology contributes significantly to the quality of the dissertation produced. Factors that influence the effectiveness of learning include lecturer involvement, availability of learning resources, and student motivation. This study recommends the development of a more interactive curriculum and the use of technology in learning research methodology to improve students' abilities in compiling quality dissertations. Thus, the results of this study are expected to provide a positive contribution to the development of postgraduate programs in Indonesia.